A case of steroid-resistant nephrotic syndrome associated with systemic lupus erythematosus. (June 2014) - Ito, I; Nishida, M; Morioka, S; Nozaki, T; Imamura, T; Morimoto, A; Akioka, S; Sugimoto, T; Hamaoka, K; Hosoi, H
We report on an 11-year-old girl who developed steroid-resistant nephrotic syndrome (NS) at the onset of systemic lupus erythematosus (SLE), and clinical and renal histological findings suggested that her NS would be associated with SLE-related podocytopathy. Although initial treatment with intravenous pulse methylprednisolone was ineffective, following treatment with cyclosporine and an angiotensin receptor blocker was effective for her nephrotic proteinuria. She had developed posterior reversible encephalopathy syndrome (PRES), and mycophenolate mofetil (MMF) was started instead of cyclosporine. At present, 45 months after the onset, she is in remission of both NS and SLE. This case indicates that NS associated with SLE-related podocytopathy should be included in the spectrum of glomerulopathy accompanying SLE, also in the pediatric population.